2021
DOI: 10.1097/md.0000000000027869
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of microRNA-155 in active tuberculosis

Abstract: Background: Tuberculosis (TB) is a preventable and treatable disease, but the increased mortality and morbidity associated with TB continues to be a leading cause of death globally. MicroRNA (miRNA)-155 has been recognized as a marker of many lung diseases. However, the effectiveness of this marker for diagnosing TB remains unclear.Methods: A detailed search (updated on February 6, 2021) of literature published in the Wanfang database, EMBASE, PubMed, CNKI, and Cochrane Library was conducted to identify eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Another miRNA involved in susceptibility is miR-155 , in charge of increasing the Th1 response in the form of regulation of IFN-γ secreting CD4 T cells, without which B6 mice became more susceptible [ 202 ]. miRNA-223 is upregulated in human active tuberculosis cases and inhibits apoptosis of macrophages [ 203 ], while some authors have suggested miRNA-155 as a possible biomarker for diagnosis of active tuberculosis, especially in children [ 204 ].…”
Section: Tuberculosis: Knowing the Enemymentioning
confidence: 99%
“…Another miRNA involved in susceptibility is miR-155 , in charge of increasing the Th1 response in the form of regulation of IFN-γ secreting CD4 T cells, without which B6 mice became more susceptible [ 202 ]. miRNA-223 is upregulated in human active tuberculosis cases and inhibits apoptosis of macrophages [ 203 ], while some authors have suggested miRNA-155 as a possible biomarker for diagnosis of active tuberculosis, especially in children [ 204 ].…”
Section: Tuberculosis: Knowing the Enemymentioning
confidence: 99%
“…Secondly, a detailed elucidation of protective immune response against the pathogen is missing, and hence establishment of reliable co-relates of protection remains a major challenge. Last but not the least, given the heterogenicity of host-pathogen interactions in humans and animal models, there have been discrepancies in the immunogenicity when the vaccine candidate testing moves from preclinical to clinical stage making the process incredibly challenging (Li et al, 2020) (Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Simple yet effective tools like—positive or negative likelihood ratios have been used to identify microRNAs as reliable diagnostic marker against TB (X. Li et al, 2021 ). In a study, multivariate logistic model and relevance vector machine models were used to profile microRNAs to different categories of TB infection in adults and in children with the authors suggesting prospects of this approach in assigning miRNA signatures to different population ( Miotto et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, PTB accounts for 75% of TB cases and greatly increases mortality 4 . Symptom assessment, radiological examination, and microbiological examination are the commonly used diagnostic methods, but they have different drawbacks 5 . For example, Mtb culture is established as the gold standard for TB diagnosis, but it takes plenty of time and does not effectively prevent transmission and infection.…”
Section: Introductionmentioning
confidence: 99%
“…4 Symptom assessment, radiological examination, and microbiological examination are the commonly used diagnostic methods, but they have different drawbacks. 5 For example, Mtb culture is established as the gold standard for TB diagnosis, but it takes plenty of time and does not effectively prevent transmission and infection. Therefore, understanding the pathogenesis of PTB and finding effective biomarkers for the early diagnosis will help in the prevention and treatment of PTB.…”
Section: Introductionmentioning
confidence: 99%